2010
DOI: 10.1111/j.1468-036x.2008.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversification, Refocusing and Firm Value

Abstract: At any point in time a firm faces three restructuring choices: diversify, refocus, or do nothing. This study analyses the causes and the consequences of these actions in a unified framework using the appropriate methodologies. Various factors, such as firm's characteristics and multinational nature, its industry's characteristics, its exchange and index inclusion, and divested (or acquired) segment(s)' industry conditions, are considered as the determinants of the diversifying and the refocusing decisions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 59 publications
1
25
0
1
Order By: Relevance
“…These results are consistent with the hypotheses in Section 3.1 and with previous studies (i.e Gibbs 1993;. Berger and Ofek 1996;Denis and Kruse 2000;Haynes et al 2003;Colak and Whited 2006;Colak 2010).…”
supporting
confidence: 95%
See 2 more Smart Citations
“…These results are consistent with the hypotheses in Section 3.1 and with previous studies (i.e Gibbs 1993;. Berger and Ofek 1996;Denis and Kruse 2000;Haynes et al 2003;Colak and Whited 2006;Colak 2010).…”
supporting
confidence: 95%
“…A C C E P T E D ACCEPTED MANUSCRIPT Penman (2012) and Colak (2010) demonstrate that an increased number of firms undertake divestitures when economic conditions suffer a downturn (such as due to the bursting of the technology and internet bubbles in 2001 and afterwards). The effect of the economic recession is measured by a dummy related to the Gross Domestic Product in the twelve months prior to month t ‫ܲܦܩ(‬ ௧ି12 ).…”
Section: A N U S C R I P Tmentioning
confidence: 98%
See 1 more Smart Citation
“…There are studies reporting a positive and linear relationship between the level of PD and performance (e.g., Chang & Hong, 2002;Miller, 2006). There are also studies that find a negative and linear relationship (e.g., Braakmann & Wagner, 2011;Tongli, Ping, & Chiu, 2005), while others find no significant relationship (e.g., Çolak, 2010;Gort, 1962;Montgomery, 1985). Other studies have examined the difference between related and unrelated diversification (e.g., Christensen & Montgomery, 1981;Rumelt, 1974Rumelt, , 1982Tallman & Li, 1996).…”
Section: Résumémentioning
confidence: 99%
“…Next, concerning product diversification measurement, certain scholars (Pandya & Rao, 1998;Tan, Chang, & Lee, 2007) measured this strategy using Rumelt's (1974) diversification classes, while others depended on using continuous measures such as Diversification Entropy Measure (David, O'Brien, Yoshikawa, & Delios, 2010;Singh, Mathur, Gleason, & Etebari, 2001) or Herfindahl Index (Çolak, 2010;Fukui & Ushijima, 2006). The use of different measurement methodologies for geographic diversification such as foreign sales ratio (Capar & Kotabe, 2003;Geringer, Beamish, & daCosta, 1989), geographic entropy measure (Hitt et al, 1997), along with many others have also been frequently observed in the history of literature on the field.…”
Section: A Comment On Methodologiesmentioning
confidence: 99%